THE COMPETITIVENESS TRAINING OF HIGHER EDUCATIONAL ESTABLISHMENTS IN ACCORDANCE WITH THE LABOR MARKET NEEDS - O. Nosova; O. Makovoz (Kherson State University, 2011)
The existing standards for higher educational establishments in Ukraine and consequences of their use for the labour market have been analyzed in the article. The necessity of taking into consideration the labour market needs and planning of specialists training by higher educational establishments has been determined. The perspectives for further research have been considered.